Dinitro-o-cresol induces apoptosis-like cell death but not alternative oxidase expression in soybean cells - Aranha, Márcia M (Journal of plant physiology, 2007)
In plants, programmed cell death is thought to be activated during differentiation and in response to biotic and abiotic stresses. Although its mechanisms are far less clear, several morphological and biochemical features have been described in different experimental systems, including DNA laddering and cytosolic protease activation. Moreover, plant mitochondria have an alternative terminal oxidase (AOX), which is thought to be involved in protection against increased reactive oxygen species production, perhaps representing a mechanism to prevent programmed cell death. In this study, we analysed cell death induced by the herbicide dinitro-o-cresol (DNOC) in soybean (Glycine max) suspension cell cultures and evaluated biochemical and molecular events associated with programmed cell death. AOX capacity and expression were also determined. DNOC-treated cells showed fragmented nuclear DNA as assessed by an in situ assay that detects 3'-OH ends. In addition, specific colorimetric assays and immunoblot analysis revealed activation of caspase-3-like proteins and release of cytochrome c from mitochondria, respectively, confirming the apoptotic-like phenotype. Surprisingly, AOX capacity and protein levels decreased in DNOC-treated cells, suggesting no association between cell death and AOX under these experimental conditions. In conclusion, the results show that DNOC induces programmed cell death in soybean cells, suggesting that plants and animals might share similar pathways. Further, the role of AOX in cell death has not been confirmed, and may depend on the nature and intensity of stress conditions